The Legitimacy of Global Social Indicators : Reconfiguring Authority, Accountability and Accuracy - Nelken, David (Les Cahiers de droit, 2018)
This paper was written in response to an invitation by the organisers of the 2016 Brussels “colloquium on inter-normativity” to address “law-like” or “law related” transnational normative phenomena so as to assess inter alia, “the validity and legitimacy of social indicators such as university rankings, credit rating agencies indicators, rankings of legal regimes and other attempts to provide indicators in areas of social law, human rights law and business law”. The first part discusses the definition of global social indicators, how they relate to other normative materials — from law to algorithms — and what could be meant by asking for them to be legitimate. The second part then examines the implications of debates about and descriptions of indicators for three key aspects of legitimacy : authority, accountability and accuracy. It suggests that indicators are indeed assessed in terms of these criteria but that they also serve to reconfigure and transform them. As noted in the concluding section the paper argues that the relationship between the three aspects of legitimacy identified needs further examination, but that the challenge they pose is more fundamental. Objections to indicators turn on the ideas of the good society they embody, the part they play in constructing the relationship between more or less economically developed societies, and the kind of governance model they reflect — for example their tendency to substitute technicalities for political participation and their link to audit culture. On the other hand, even if caution is needed in endorsing the use of indicators in projects of governance, they do often have advantages of publicness, contestability and openness to violation when compared to the spread of algorithmic regulation.